In vitro antiplasmodial activity, LC-MS analysis, and molecular docking studies of bioactive compounds from Tetrapleura tetraptera (Fabaceae) fruits - Sherif Hamidu; Latif Adams; Patrick Kwabena Oduro; Felix Kwame Zoiku; Abigail Aning; Eunice Ampem-Danso; Janet Abena Ampofo; Michael Afiadenyo; Siobhan Moane; Michelle McKeon Bennett; Kwadwo Asamoah Kusi; Dorcas Obiri -Yeboah (Scientific African, 2023)
Malaria continues to be a major public health concern, particularly for children and pregnant women in areas where the disease is endemic. Developing safe and efficient antimalarial therapies to fight the disease is essential. Medicinal plants represent a potential source for the development of new antimalarial drugs. Tetrapleura tetraptera is a plant native to West Africa and traditionally used to treat several diseases including Malaria. Here, we investigated the antiplasmodial activities of T. tetraptera fruit extracts against the chloroquine-sensitive (Pf3D7) and chloroquine-resistant (PfDD2) strains of Plasmodium falciparum in vitro using SYBR green assay. In addition, the antioxidant potential of the fruit extracts was also determined. LC-MS analysis was carried out to identify the bioactive compounds in the extracts. Molecular docking studies provide significant prima facie evidence of inhibition hence, to evaluate the potential inhibition of Plasmodium falciparum dihydroorotate dehydrogenase (PfDHODH), a validated malaria drug target, the identified compounds were docked against PfDHODH. Strong antiplasmodial activities were demonstrated by the ethyl acetate and ethanolic extracts of T. tetraptera fruit, with IC50 values of 16.12 ± 0.04 µg/mL and 2.06 ± 0.02 µg/mL against the Pf3D7 strain, respectively. In the DPPH radical scavenging experiment, the ethanolic extract revealed considerable antioxidant activity with an EC50 value of 0.21 ± 0.82 mg/mL. Seven bioactive compounds were identified in the extract using LC-MS analysis. N-Methyl-1H-indole-3-propanamide (I), Tazolol (II), and Isopentyl salicylate (III) were identified as potential inhibitors of PfDHODH with high binding affinities ranging from -32.08 to -30.69 kcal/mol. The potential lead compounds also interacted with Gly181, Leu531, and Arg265, which are critical amino acid residues in the catalytic activity of PfDHODH. These findings support the traditional use of T. tetraptera fruit extracts for the treatment of malaria and as promising avenues for antimalarial drug development.